Influence of Artificial Intelligence and Robotics Awareness on Employee Creativity in the Hotel Industry - Wang, Hui; Zhang, Han; Chen, Zhezhi; Zhu, Jian; Zhang, Yue (Frontiers in psychology, 2022)
The current literature in artificial intelligence and robotics awareness (AIRA) focused on the dark side of AIRA. Accordingly, this study sheds light on the positive effect of AIRA on employee creativity by exploring how and when hotel employees may take proactive behavior facing the threat of AI and robotics to further stimulate creativity. Based on the work adjustment theory (TWA) and the locus of control theory, this study constructs a moderating multiple mediation model to explain the influence of AIRA on employee creativity, in which active learning and task crafting are used as mediating variables, and locus of control is used as moderating variable. Data collected from 264 employees in a Chinese hotel are used for empirical analysis. Results show that (a) AIRA indirectly positively affects employee creativity via active learning and task crafting and (b) Locus of control not only moderates the mediating effect of active learning between the relationship of AIRA and employee creativity but also moderates the mediating effect of task crafting between the relationship of AIRA and employee creativity. The theoretical and practical implications are discussed.